Greater Occipital Nerve Decompression for Occipital Neuralgia. Issue 5 (July 2018) - Jose, Anson; Nagori, Shakil Ahmed; Chattopadhyay, Probodh K.; Roychoudhury, Ajoy
Abstract : Abstract: The aim of the study was to evaluate the effectiveness of greater occipital nerve decompression for the management of occipital neuralgia. Eleven patients of medical refractory occipital neuralgia were enrolled in the study. Local anaesthetic blocks were used for confirming diagnosis. All of them underwent surgical decompression of greater occipital nerve at the level of semispinalis capitis and trapezial tunnel. A pre and postoperative questionnaire was used to compare the severity of pain and number of pain episodes/month. Mean pain episodes reported by patients before surgery were 17.1 ± 5.63 episodes per month. This reduced to 4.1 ± 3.51 episodes per month ( P  < 0.0036) postsurgery. The mean intensity of pain also reduced from a preoperative 7.18 ± 1.33 to a postoperative of 1.73 ± 1.95 ( P  < 0.0033). Three patients reported complete elimination of pain after surgery while 6 patients reported significant relief of their symptoms. Only 2 patients failed to notice any significant improvement. The mean follow-up period was 12.45 ± 1.29 months. Surgical decompression of greater occipital nerve is a simple and viable treatment modality for the management of occipital neuralgia. Abstract : Supplemental Digital Content is available in the text